2020
DOI: 10.1101/2020.07.03.20146076
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No official help is available - experience of parents and children with congenital heart disease during COVID-19

Abstract: Purpose of the study The purpose was to explore the experience, information, support needs and decision-making of parents with congenital heart disease (CHD) during the COVID-19 crisis. Study design On-line survey design Setting An on-line survey with open/closed questions to explore the experiences of parents of children, as well as children and young people (CYP) with CHD during the COVID-19 crisis Patients Parents of children with CHD and CYP Results 184 parents and 36 CYP completed the survey. Pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 13 publications
2
13
1
Order By: Relevance
“…Findings from the SHARE studies exploring the views of parents of children with cancer, and parents of children with congenital heart disease found that parents were worried about the virus in the context of their child's disease condition. 3 This is a similar finding to parents views in the preterm population. However, parents within the preterm survey reported additional concerns about their face being covered by a mask, and the subsequent ability to bond with their baby.…”
Section: B R I E F R E P O R T Preterm Birth During the Covid-19 Pand...supporting
confidence: 88%
See 1 more Smart Citation
“…Findings from the SHARE studies exploring the views of parents of children with cancer, and parents of children with congenital heart disease found that parents were worried about the virus in the context of their child's disease condition. 3 This is a similar finding to parents views in the preterm population. However, parents within the preterm survey reported additional concerns about their face being covered by a mask, and the subsequent ability to bond with their baby.…”
Section: B R I E F R E P O R T Preterm Birth During the Covid-19 Pand...supporting
confidence: 88%
“…Many parents felt there was a significant psychological and emotional impact due to COVID‐19 restrictions on the birthing experience and afterwards and on their neonatal intensive care journey. Findings from the SHARE studies exploring the views of parents of children with cancer, and parents of children with congenital heart disease found that parents were worried about the virus in the context of their child's disease condition 3 . This is a similar finding to parents views in the preterm population.…”
mentioning
confidence: 59%
“…94 Eighteen (25%) were medium-quality; 13 cross sectional, 49-51,53,55,57,58,60,66,68,70,75,77 and 5 pre-post studies. 85,86,88-90 Nine (13%) were low-quality; 1 cohort, 45 3 cross sectional, 47,63,69 and 5 pre-post studies 79-81,84,87…”
Section: Resultsmentioning
confidence: 99%
“…Two cross-sectional UK studies, of cancer 48 and congenital heart disease, 63 found widespread marked parental concerns about the safety of their CYP and that 70-85% of parents believed that hospitals were not safe places for their child, anxieties that were shared by their CYP. Whilst one LQ Italian study found that 25% of CYP with IBD suspended or delayed immunoregulatory treatment against medical advice, 84 a HQ English study found that only 2.3% of parents had reduced the amount of cancer chemotherapy they gave their child.…”
Section: Resultsmentioning
confidence: 99%
“…27 A study that included 220 parents of CHD patients and children diagnosed with CHD showed that both were worried due to the lack of pediatric information and guidance, and were disappointed with the adult information available. 28 Also, the physical activity of CHD children was reduced compared to 2019 and the era before the COVID-19 pandemic and if this persists, it will affect their health. 29…”
Section: Impact Of Covid-19 On Chd Patientsmentioning
confidence: 99%